Konflik dalam Penentuan Dana Bagi Hasil antara Pemerintah Pusat dan Pemerintah Propinsi Kalimantan Timur - Tenti Kurniawati (Jurnal Ilmu Sosial dan Ilmu Politik, 2012)
This paper attempts to explain two basic analyzes related to the central conflict of Revenue Sharing between East Kalimantan Province with the central government. Firstly, the factor in revenue-sharing conflict between producing regions and the central government. The decentralization policy which is followed by fiscal decentralization makes the revenue sharing obtained under Law No.33 of 2004 on Financial Balance. Unfortunately, the policy is felt to be unfair to the area, because it is not comparable to the impact of the area, and there is no positive correlation to the public welfare. Secondly, the impact of the conflict other than to bear the social and environmental impact on natural resources exploitation also the potential of threatening disintegration. Vertical conflict between regional and central government, it can affect the horizontal conflict if the maintenance of the conflict is not good and don’t find the best resolution.